DAMPAK KERJASAMA PERDAGANGAN INDONESIA - INDIA DAN DEPRESIASI RUPIAH TERHADAP KINERJA EKSPOR MINYAK SAWIT - Syahputra, Dwi; Jamilah, Jamilah; Mawardati, Mawardati (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2021)
The study aims to analyse the impact of Indonesia-India trade cooperation and Rupiah Depreciation on Indonesia's Palm Oil Export Performance. The research method uses a simultaneous equation system model and is estimated by the 2 SLS method. Time Series data used data from 2000-2018. The results showed that Indonesia's palm oil exports to India fluctuated but showed an increasing trend (2000-2018). It is suspected that the performance of Indonesian CPO exports to India is influenced by India's import tariff reduction policy and Indonesia's CPO production. Rupiah depreciation was able to increase Indonesia's CPO exports to India, but the increase in CPO exports was unable to encourage an increase in domestic CPO prices and production. On the other hand, the increase in Indonesian palm oil exports was able to increase the price and production of domestic palm oil.